MANAJEMEN KETENAGAAN DALAM MENINGKATKAN KINERJA GURU DAN TENAGA KEPENDIDIKAN DI MI NU MIFTAHUL FALAH CENDONO DAWE KUDUS - Ulin Ni’am; Barowi Barowi; Moh Nasuka; Munasir Munasir (Intelegensia : Jurnal Pendidikan Islam, 2020)
AbstractThe purpose of this research is to determine the quality of planning, organizing, directing, and superviisng the personnel at MI NU Miftahul Falah Cendono Dawe Kudus and to determine factors that influence planning, organizing, and supervising at MI NU Miftahul Falah Cendono Dawe Kudus. This research uses qualitative descriptive research which was carried out at MI NU Miftahul Falah Cendono Dawe Kudus. Data is collected by observation, interview, and documentation. Data analysis is by data collection, data reduction, data presentation, and data verification. Based on the result of this research found that: 1) Planning of personnel is carried out by determining number of employee in work unit. 2) Organization including recruitment, selection and proper compensation. 3) Directing is done by providing development and coaching programs. 4) Supervising is done by supervising and performance evaluation. Furthermore, there are 2 factors that influence personnel management, namely the management process itself and external factors in the form of technological, economic, customer, competitor, legal, and political.   Keywords: Personnel Management; Teacher; Educational Staff